The Religious Forms of the Elementary Life: Durkheim Revisited - Turner, David H. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1993)
In Durkheim’s view religion is advanced insofar as it has given way to the dictates of science and rationalism. I argue here that religion may well be defined by its emphasis on the sensational and imaginative rather than the mental or intellectual, and that it is in these terms that religious development should be measured. The article develops the view that Australian Aborigines, far from the least developed society and religion as Durkheim imagined, should be viewed as having the greatest development of religion, as well as an extraordinary form of organic solidarity based on their religion.